Albizia procera Benth, a New Host forCercospora albiziae - Nath, V.; Harsh, N. S. K.; Tivari, C. K.; Rehill, P. S. (Indian Forester, 1988)
Cercospora albiziae Kar&Mandal has been described on a new host Albizia procera Benth.